Association between coa gene and enterotoxin gene in S. aureus from dairy cattle in Brazil - VALMORBIDA, Mylena Karoline; CARDOZO, Marita Vedovelli; ALMEIDA, Camila Chioda de; PEREIRA, Natália; DEZEN, Diogenes; ASSIS, Marcella Zampoli de; VERBISCK, Newton Valério; GRIEBELER, Eliete; PIZAURO, Lucas José Luduverio; ÁVILA, Fernando Antônio de (Food Science and Technology, 2023)
Staphylococcus aureus is an important agent in bovine mastitis, and some specific virulence factors may be implicated in this disease. Therefore, this study aimed to investigate the importance of the presence of coagulase, superantigens, genotypic and phenotypic resistance, and pulsotypes in 65 S. aureus isolates from bovine clinical and subclinical mastitis in the Southeast of Brazil. A high correlation was observed between the genes coa and see, as well as between the sei and the see and seh. High resistance rates were observed for penicillin (95.4%), tetracycline (89.2%), cefoxitin (86.1%), oxacillin (84.6%), erythromycin (84.6%), clindamycin (84.6%), chloramphenicol (81.5%), ceftriaxone (80.0%), and ampicillin (80.0%). Analysis of antimicrobial resistance profiles showed that 89.2% of isolates were multi-drug-resistant. No mecA-positive S. aureus isolates were detected. It was observed that seven isolates were resistant to all the β-lactam tested while being susceptible to cefoxitin, which could be indicative of borderline methicillin resistance in S. aureus⁠. High genetic diversity with no specific virulence profile being predominant was observed. Thus, this study observed a high correlation between the coa and enterotoxins genes, and demonstrates that there is no predominant pulsotype causing intramammary infection and that there is a high rate of antibiotic resistance in S. aureus isolates from dairy farms in the southeast regions of Brazil.